1995
DOI: 10.1007/bf02208676
|View full text |Cite
|
Sign up to set email alerts
|

Compliance of the proximal stomach and dyspeptic symptoms in patients with type I diabetes mellitus

Abstract: this study showed that the compliance of the proximal stomach is increased in diabetic patients with autonomic neuropathy and gastrointestinal symptoms. This abnormality, probably due to autonomic neuropathy, is associated with increased symptom generation during gastric distension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
23
0
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 125 publications
(26 citation statements)
references
References 22 publications
2
23
0
1
Order By: Relevance
“…Even though most patients exhibited a response to botulinum toxin in this study, a substantial number of individuals derived no benefit. This observation is consistent with studies that have characterized other potential pathogenic factors in symptom production in gastroparesis including impaired relaxation of the gastric fundus, alterations in perception of gastric distention, and abnormal burst contractile patterns in the small intestine [22][23][24][25].…”
Section: Discussionsupporting
confidence: 91%
“…Even though most patients exhibited a response to botulinum toxin in this study, a substantial number of individuals derived no benefit. This observation is consistent with studies that have characterized other potential pathogenic factors in symptom production in gastroparesis including impaired relaxation of the gastric fundus, alterations in perception of gastric distention, and abnormal burst contractile patterns in the small intestine [22][23][24][25].…”
Section: Discussionsupporting
confidence: 91%
“…Normally, the proximal stomach relaxes during eating to accommodate the ingested food without producing a large increase in gastric pressure and discomfort. This reflex is a consistent physiologic response in the healthy, whereas in patients with upper gastrointestinal symptoms, impairment in gastric accommodation is frequently observed [8][9][10][15][16][17][18][19]. Impaired gastric accommodation has been linked to upper gastrointestinal symptoms such as early satiety.…”
Section: Discussionmentioning
confidence: 99%
“…Impaired gastric accommodation has been linked to upper gastrointestinal symptoms such as early satiety. Patients with this abnormality report more upper gastrointestinal symptoms after a meal or during gastric distension than healthy controls [15,17,18]. Experimental inhibition of the accommodation could induce dyspeptic symptoms even in healthy subjects [11], whereas restoring gastric accommodation with a fundus relaxing agent improved meal-induced satiety in patients with functional dyspepsia [9].…”
Section: Discussionmentioning
confidence: 99%
“…After a 15-min rest period minimal distension pressure (MDP) was determined by increasing the pressure in the bag in 1-mm Hg increments. MDP was defined as the lowest pressure level that provided a mean intrabag pressure of 30 ml (8,12). Thereafter intrabag pressure was set at 1 mm Hg above MDP (MDP + 1) for the remainder of the study.…”
Section: Study a Experimental Design And Barostat Measurementsmentioning
confidence: 99%
“…Abnormal postprandial proximal gastric accommodation has been reported in several studies. Most studies that have investigated gastric accommodation have made use of the barostat technique to quantify the increase in volume of the proximal stomach after meal ingestion in conditions (7)(8)(9)(10) such as functional dyspepsia (11) and diabetes mellitus (8,12). Reduced proximal gastric accommodation has been reported to be related to symptoms such as early satiety and weight loss (11), although other studies have not confirmed this relation (13).…”
mentioning
confidence: 99%